City Cultural Code: Identification Problem - Кравченко, О. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. Investigating the peculiarities of the functioning of the city and its culture in the industrial era, it is possible to outline the place and role of cultural code in this process. The aim and the tasks of the study is to conduct a cultural and philosophical study of the city's cultural code and the self-identification of urban residents into industrial era and its impact on the further transformation of the city. Research methods. The article uses cultural-historical and socio-cultural approaches, a method of semiotic and cultural-semantic analysis. Research results. The transition from a sedentary and cyclical time in traditional society to a non-linear time in industrial life radically alters man’s existence, within which the question of identity is raised. Thus, the meaningful "processing" of the city and its essence form both the cultural and ontological basis of identity construction. The formation and historical development of urban space largely determines the cultural values and motives of human behavior in society. However, the heterogeneity of this process suggests the need to study the impact of urban space on the cultural identification of man in modern society. The very process of human perception of any cultural tradition is associated with the definition of the environment and the stages of its formation. Discussion. Cultural code of the city is filled with meanings, ideas symbolic place, or thing for its citizens, something the city is associated. Each urban dweller and inhabitant in the perception of the city your "set" of cultural codes that intersect with the codes of other people, creating a collective image of the city, and this "set" of the individual codes. Conclusions. Cultural features of the area code in the context of cultural-historical processes showed that each city has its own unique code, their identity and semantics, which have been formed throughout the historical development of the city. In them the whole culture is concentrated, from architectural monuments, theaters, museums, theme parks, places of leisure, and ending with modern art-magazines, innovative works of art. Each city has its own traditions, its own emblem and its own anthem. It all creates a unique city code, is not inherent in any other city. The interaction of the system images in their entirety leads to the formation of the image of the city.